Heart rate acquisition and threshold-based training increases oxygen uptake at metabolic threshold in triathletes: A pilot study - Neufeld, E. V.; Wadowski, J.; Boland, D. M.; Dolezal, B. A.; Cooper, C. B. (International Journal of Exercise Science, 2019)
Exercise intensity is a critical component of the exercise prescription model. However, current research employing various non-specific exercise intensity protocols have reported wide variability in maximum oxygen uptake (VO2max) improvement after training, suggesting a present lack of consensus regarding optimal heart rate (fC) training zones for maximal athletic performance. This study examined the relationship between percentage of time (%time) spent training between the metabolic (VO2Theta) and ventilatory thresholds (VETheta) and the resultant change in markers of aerobic performance. Thirteen (6 males) collegiate club-level triathletes were recruited for eight weeks of remote fC monitoring during all running and cycling sessions. Participants donned a forearm-worn optical fC sensor paired to a smartphone that collected and stored fCs. Subjects were categorized into Low and High groups based on %time spent training between the VO2Theta and VETheta. Significant increases were observed in relative VO2max (P = 0.007, g = 0.48), VO2Theta (P = 0.018, g = 0.35), and VETheta (P = 0.030, g = 0.29) from baseline after eight weeks for both groups. A 95% bootstrapped confidence interval that did not include zero (-0.38, -0.03; g = 1.26) revealed a large and significantly greater change in VO2Theta in the High group (0.37 ± 0.15 L/min) versus the Low group (0.17 ± 0.14 L/min). No significant differences were observed in other variables between groups. Increasing triathletes` %time spent exercising between VO2Theta and VETheta may optimize increases in VO2Theta after eight weeks of training.